Reimplantation of a bicuspid aortic valve with simultaneous correction of the aortic ductus diverticulum - S. Y. Boldyrev; V. N. Suslova; V. A. Pekhterev; K. O. Barbukhatti; V. A. Porhanov (Вестник хирургии имени И.И. Грекова, 2020)
Reimplantation of a bicuspid aortic valve is relatively rare, and in combination with a the correction of aortic ductus diverticulum is a casuistic case. We present the experience of simultaneous reimplantation of bicuspid aortic valve with the correction of aortic ductus diverticulum. A 53-year-old male with a diagnosis of ascending aortic aneurysm, bicuspid aortic valve type 0 by Sievers with failure, aortic ductus diverticulum. The patient underwent an aortic valve reimplantation operation using the vascular prosthesis UniGraft № 36 and exoprosthetics of the descending aorta in the area of diverticulum. In the postoperative period, satisfactory aortic valve function was observed on ultrasound of the heart. The patient was discharged on the 15th day.